Calon Perseorangan dalam Pemilihan Umum Kepala Daerah - Warjiyati, Sri (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2014)
Abstract: This article discusses the individual candidate in the general election of regional head in political jurisprudence perspective. Before the Mahkamah Konstitusi?s decision No. 5/PUU-V/2007 pointed out, the individual candidate could have enter the two political institutions; first, in the 2004 general election, the individual candidate competed to get into the institution of the Regional Representative Council of the Republic of Indonesia; second, Undang-Undang No. 11 tahun 2006 regarding with the Government of Aceh where the individual candidate could compete with the candidates promoted by the national political party in electing the regional head in all over Aceh. The decision of Mahkamah Konstitusi No. 5/PUU-V/ means that the local head election held in various regions can include the individual independent candidate. In political jurisprudence perspective, mechanism of the individual candidacy in the election has already in accordance with the concept of maslahah al-?ammah ie. hifdz al-ummah.  In this case, any of the individual independent candidates who nominate themselves as the regional head cannot be discriminated and they deserve the right to nominate to be in line with the Mahkamah Konstitusi?s decision.Keywords: Candidate, individual, local election, jurisprudence, siyasah